(untitled) (Research, Society and Development, 2022)
Cutaneous Leishmaniasis (CL) is an important neglected tropical disease, that reaches about 900 thousand to 1.5 million people annually, mainly in Brazil. The present study aimed to characterize these lymphocyte populations and the expression of the CD45RO marker profile in patients with CL. We evaluated CD4+, CD8+, double-positive (DP) and double-negative (DN) T cells and their expression of CD45RO in Cutaneous Leishmaniasis patients, divided into three groups: before treatment (BT), posttreatment (PT) and subclinical (SC). CD4+ T cells had a higher percentage in PT and SC groups when compared to the control group (CT). CD4+ T cells presented a greater expression of CD45RO in BT and PT groups compared to the SC group, that had a lower expression compared with the CT. CD8+ T lymphocytes had a higher percentage in BT when compared with CT and a greater expression of CD45RO when compared to PT, SC and CT groups. We did not observe any statistical significance in the percentage of the DP and DN lymphocytes, however, we noticed that the DP lymphocytes presented a lower expression of CD45RO in the SC group when compared to the CT group, whereas the DN lymphocytes showed a greater expression of CD45RO in the BT group when compared with the other groups. CD4+ T cells appear to be protective in these patients and CD8+ T lymphocytes seem to be associated to pathogenesis, while DP CD45RO+ and DN CD45RO+ lymphocytes appear to play a dual role.